IMPLIKASI HUKUM TENTANG PENYALAHGUNAAN TEKNOLOGI DEEPFAKE TERHADAP KEJAHATAN IDENTITAS DIGITAL - Aprillia, Nabila; Khasanah, Dian Ratu Ayu Uswatun; Pongantung, Ronald Jolly (Universitas Stikubank, 2025)
The development of artificial intelligence technology has given birth to deepfake technology which has the potential to be misused to damage a person's digital identity. This research aims to analyze the mode of misuse of deepfake technology in Indonesia, examine its legal implications based on applicable laws and regulations, and examine the urgency of special regulation of deepfake in the Indonesian legal system. Applicable, as well as examining the urgency of special arrangements against deepfake in the Indonesian legal system. The research method used is normative juridical legal research with statutory and conceptual approaches, and data collection is carried out through literature study of primary, secondary, and tertiary legal materials tertiary. The results show that deepfake abuse can take the form of spreading fake videos, face forgery and digital identity-based fraud that harms victims socially, legally and psychologically. Although several articles in the ITE Law, Personal Data Protection Law, and Criminal Code can be used to charge perpetrators, these regulations have not specifically and explicitly regulated the characteristics and technical aspects of deepfake-based crimes. This creates obstacles in law enforcement and victim protection. Therefore, it is necessary to establish special regulations or amend existing laws so that the legal system in Indonesia is able to answer the challenges of deepfake technology appropriately, fairly, and effectively.